Efektivitas Air Kelapa Hijau untuk Mengurangi Dismenore Primer Pada Remaja Putri di Puskesmas Binuangeun Lebak- Banten - Suryani, Elsa; Gapmelezy, Ezzy (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Based on the Lebak District Health Office's adolescent report in 2022, there were 1178 cases of menstrual disorders in adolescents. Based on reports from the youth program at the Binuangeun Inpatient Health Center UPTD, as of November 2022, 43.5% of teenagers experienced dysmenorrhea or menstrual disorders. The way to treat dysmenorrhea is pharmacological and non-pharmacological, non-pharmacological using green coconut water with the highest K element content. Green coconut water contains calcium 11-25 mg/l, magnesium 6-22 mg/l, potassium 1-8 mg/l, sodium 9-25 mg/l, bicarbonate 71-187 mg/l, chioride 1-25 mg/l l, sulfate 2-33 mg/l, silica 62-87 mg/l, TDS 88-190 mg/l, pH 6.7-7.2 To determine the effectiveness of green coconut water in reducing primary dysmenorrhea pain in adolescents girls at the Binuangeun Community Health Center, Wanasalam District, Lebak Regency, Banten Province in 2024. This research design used a quasi-experimental with pre-test and pot test non-equivalent control group design. This study aims to analyze the differences between the 2 groups regarding the timing of administration of green coconut water, in the treatment group it was given 2 days before menstruation until 2 days of menstruation and in the control group on the first day of menstruation until 2 days of menstruation. The population of this study was teenagers with a sample of 60 people. The research was conducted in June-July 2024. The average reduction in the pain scale in the treatment group was found to be a mean of 2.03 - median of 2, a standard deviation of 0.718 with the lowest pain being 1 and the highest being . The average decrease in pain scale in the control group was mean 3.33, -median 3, standard deviation 0.661 with the lowest pain 2 and the highest 4. Results using the Wilcoxon Signed Rank Test at a significance level of 95%, obtained a ρ - value of more than 0.000 less than a significant value of 0.05 that there is a significant effect of reducing pain between the intervention group and the control group. Giving green coconut water to reduce primary dysmenorrhea is more effective given 2 days before menstruation until 2 days of menstruation. Keywords: Adolescent Primary Dysmenorrhea, Green Coconut Water    ABSTRAK Berdasarkan laporan remaja Dinkes Kabupaten Lebak tahun 2022 terdapat 1178 kasus gangguan haid pada remaja. Berdasarkan laporan program remaja di UPTD Puskesmas Rawat Inap Binuangeun sampai dengan November 2022 terdapat 43,5% remaja mengalami dismenore atau gangguan haid. Cara penanganan dismenore yaitu secara farmakologi dan non farmakologi, non farmakologi menggunakan air kelapa hijau dengan kandungan unsur K paling tinggi. Air kelapa hijau mengandung kalsium 11-25 mg/l, magnesium 6-22 mg/l, kalium 1-8 mg/l, natrium 9-25 mg/l, bikarbonat 71-187 mg/l, chioride 1-25 mg/l, sulfat 2-33 mg/l, silica 62-87 mg/l, TDS 88-190 mg/l, pH 6,7-7,2. Untuk mengetahui efektivitas air kelapa hijau terhadap pengurangan nyeri dismenore primer pada remaja putri di Puskesmas Binuangeun Kecamatan Wanasalam Kabupaten Lebak Provinsi Banten Tahun 2024. Desain penelitian ini menggunakan quasi eksperiman dengan pre test dan pot test non equivalent control group design. Penelitian ini bertujuan untuk menganalisa perbedaan dari 2 kelompok dengan waktu pemberian air kelapa hijau, pada kelompok perlakuan diberikan 2 hari sebelum mentruasi sampai 2 hari masa menstruasi dan pada kelompok kontrol pada hari pertama menstruasi sampai 2 hari masa menstruasi. Populasi penelitian ini adalah remaja dengan sampel 60 orang. penelitian dilakukan pada bulan Juni-Juli 2024. Didapatkan rata-rata penurunan skala nyeri pada kelompok perlakuan yaitu mean 2,03 -median 2, standar daviasi 0,718 dengan nyeri terendah 1 dan tertinggi . Rata-rata penurunan skala nyeri pada kelompok control yaitu mean 3,33, -median 3, standar daviasi 0,661 dengan nyeri terendah 2 dan tertinggi 4. Hasil menggunakan uji Wilcoxon Signed Rank Test pada tingkat kemaknaan 95%, didapatkan nilai ρ – Value 0,000 lebih kecil dari nilai signifikan 0,05 bahwa terdapat pengaruh signifikan penurunan rasa nyeri antara kelompok intervensi dan kelompok control. Pemberian air kelapa hijau untuk mengurangi dismenore primer lebih efektif diberikan 2 hari sebelum menstruasi sampai 2 hari masa menstrusi. Kata Kunci: Remaja Dismenore Primer, Air Kelapa Hijau